Sacred grove as remnant forest: A vegetation analysis - SAIKAT MANNA; SUMIT MANNA; TUSHAR KANTI GHORA; ANIRBAN ROY (Society for Indonesian Biodiversity, 2017)
Manna S, Manna S, Ghora TK, Roy A. 2017. Sacred grove as remnant forest: A vegetation analysis. Biodiversitas 18: 899- 908. Sacred groves are the remnants of ancient virgin forest sustaining veritable gene pool that have been gained century-long protection through the inherent cultural and religious belief of the ethnic communities. These important local biodiversity hotspots, representing the climatic climax of regional plant communities, are gradually being under threat by natural disturbances or anthropopression. Thus vegetation analysis of sacred groves is very important to find out their lineage to nearby existing forest. To reach the goal, significant plant compositional similarity between the sacred groves with changing distance was measured by 2X2 contingency analysis from presence/absence data matrix of major tree species (MTS) and major climber and liana species (MCLS) of 13 sacred groves of a particular soil zone. The observation reveals a significant gradual decrease in chi-square value with the increasing distance between the groves. Jaccard and Sorensen Coefficients for community similarity also reflect an inverse relationship of any two groves with increasing distance. Agglomeration Hierarchical Clustering (AHC) depicts that all the 74 families are found to be clustered into three significant groups. In respect of Multiple Correspondence among sacred groves, symmetric and asymmetric plots indicate that there two distinct groups have theirs within similarities among families in the groves. The plexus diagram shows a confluence zone of all the 13 sacred groves which might be the maximum probable area of an ancient riverine wood forest. The study would be helpful in restoration of threatened/degraded sacred groves and also guide in the preparation of management plan for the conservation of these relic forest fragments.